Are teenagers receiving appropriate Sex and Relationships Education and sexual health services at school to lessen the risk of teenage pregnancy? Examining the attitudes of Nottingham based school nurses and secondary school teachers. - Dodds, Elizabeth (2011)
Background Nottingham City has one of the highest teenage pregnancy rates in England. The Teenage Pregnancy Strategy was implemented in 1999. One of its aims was to improve Sex and Relationships Education (SRE) and sexual health services (SHS) in schools. However, evidence suggest that some schools do not place high priority on these topics.